Exploring Translanguaging Challenges Experienced by Teachers: A Case Study in BIPA Classes - Aini Nabila Ikhwanudin; Fuad Nabil Adzanil; Suharyadi Suharyadi (English Department - University of Sultan Ageng Tirtayasa, 2025)
This study aims to explore the perceptions and challenges of translanguaging faced by teachers in BIPA (Indonesian for Foreign Speakers) classes. Using a qualitative approach and specifically a descriptive case study design case study design, it involved in-depth interviews with four BIPA teachers. The results showed that translanguaging, which involves alternating the use of English and Indonesian, facilitates the process of learning Indonesian, especially at the beginner level. This strategy helps students understand complex materials, increases engagement, expands vocabulary, and reduces language learning anxiety. However, challenges remain, including students’ reliance on English, differences in language proficiency levels, and difficulties in teaching complex language concepts such as grammar and sentence structure. In addition, it highlights the importance of context and cultural elements in BIPA learning. Cultural elements, such as ‘catatan budaya’ handbook that includes traditional Indonesian dances and customs, help students understand the language more deeply while introducing Indonesian culture globally. In conclusion, translanguaging is an effective pedagogical strategy, but its success requires a balance between the use of English and Indonesian, as well as the readiness of teachers to manage the challenges that arise. The implications of these findings indicate the need for professional training for teachers to optimize the application of translanguaging in BIPA learning.